Optimasi Metode Ekstraksi DNA pada Melon (Cucumis melo L.) Berdasarkan Suhu, Lama Inkubasi, dan Kondisi Daun - Dewi Retnaningati (Universitas Atma Jaya Yogyakarta, 2020)
Melon is a fruit commodity that has high economic value and is in demand by the community, so it has the potential to be developed. Therefore it is necessary to study various sciences, one of which is the molecular approach. DNA is an essential element in molecular research. The right extraction technique will determine the quality and quantity of DNA produced. The temperature and incubation time applied in the DNA extraction technique, as well as the quality of the leaves as a source of plant DNA, are among the determining factors for the quality and quantity of extracted DNA, so it is necessary to carry out an assessment and optimization. This study aims to assess the optimal temperature and incubation time in extracting DNA from material (melon leaves) under different conditions. Research activities include planting melon seeds, collecting leaf samples, DNA extraction and quantitative DNA testing. The results showed that the concentration and purity of DNA extracted from cold leaves was higher than that from fresh leaves. The highest DNA concentration was obtained from the 65 ° C incubation treatment for 20 minutes, namely 2707.6 ng / μl, and the highest DNA purity was obtained from the 70 ° C incubation treatment for 10 minutes, namely 1.94 from leaf material that had been cooled overnight at a temperature of -20 ° C .